2010
DOI: 10.1186/1472-6823-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function derangement and childhood obesity: an Italian experience

Abstract: BackgroundIn recent years, there has been an increasing attention to thyroid function in paediatric obese patients. In the present study we aimed 1) to determine the prevalence of abnormally elevated thyroid-stimulating hormone (TSH) levels in Italian obese children and adolescents 2) to investigate whether hyperthyrotropinemia in obese children cardiovascular and metabolic risk factors 3) to verify if TSH elevation is reversible after weight loss.MethodsWe examined 938 obese children and adolescents (450 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
90
5
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(124 citation statements)
references
References 31 publications
18
90
5
11
Order By: Relevance
“…Contrasting results were reported by other authors who did not detect any association between TSH levels and HOMA-IR (5,14).…”
Section: δBmc-sdscontrasting
confidence: 54%
See 3 more Smart Citations
“…Contrasting results were reported by other authors who did not detect any association between TSH levels and HOMA-IR (5,14).…”
Section: δBmc-sdscontrasting
confidence: 54%
“…Taking into account previous studies where improvements in the metabolic profile only occurred in the presence of significant weight loss (i.e., a decrease > 0.5 in BMI-SDS) (4,5,23), the sample was divided into three groups according to the degree of weight loss: increase in BMI-SDS; decrease in BMI-SDS between 0 and 0.5; and decrease in BMI-SDS > 0.5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were compatible with the results of several other studies. Grandone et al found high TSH levels (>4.2mIU/ ml) in 12.8% of 938 obese children aged between 4.5-16 years [9]. In Bhowmick et al's study high TSH (>4 mIU/ml) rate was 11.7% in 308 obese children aged 6-17 years [10].…”
Section: Discussionmentioning
confidence: 99%